2014
DOI: 10.3390/md12105258
|View full text |Cite
|
Sign up to set email alerts
|

SxtA and sxtG Gene Expression and Toxin Production in the Mediterranean Alexandrium minutum (Dinophyceae)

Abstract: The dinoflagellate Alexandrium minutum is known for the production of potent neurotoxins affecting the health of human seafood consumers via paralytic shellfish poisoning (PSP). The aim of this study was to investigate the relationship between the toxin content and the expression level of the genes involved in paralytic shellfish toxin (PST) production. The algal cultures were grown both in standard f/2 medium and in phosphorus/nitrogen limitation. In our study, LC-HRMS analyses of PST profile and content in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 56 publications
5
32
0
Order By: Relevance
“…For example, the gene expression pattern for sxtA4 in A. catenella examined by RT-qPCR did not significantly change under different growth stages, even though the saxitoxin production was significantly altered [45]. A similar expression pattern was also observed in sxtA and sxtG genes in A. minutum [49]. Examination by RNA-seq on the A. catenella transcriptome also revealed that most of the putative toxin gene transcripts varied insignificantly at different toxin biosynthesis stages [46].…”
Section: Recent Insight Into Saxitoxin Biosynthesis Through Transcripmentioning
confidence: 82%
See 1 more Smart Citation
“…For example, the gene expression pattern for sxtA4 in A. catenella examined by RT-qPCR did not significantly change under different growth stages, even though the saxitoxin production was significantly altered [45]. A similar expression pattern was also observed in sxtA and sxtG genes in A. minutum [49]. Examination by RNA-seq on the A. catenella transcriptome also revealed that most of the putative toxin gene transcripts varied insignificantly at different toxin biosynthesis stages [46].…”
Section: Recent Insight Into Saxitoxin Biosynthesis Through Transcripmentioning
confidence: 82%
“…More reports for translational control in dinoflagellates were found (Table 4), leading researchers to conclude that the expression of sxt genes in dinoflagellates is controlled at the post-transcriptional or post-translational level owing to the inconsistent expression level at the transcript level documented by previous studies [46,49] and the presence of a dinoflagellate splice-leader sequence in at least two core genes for saxitoxin biosynthesis [43,44]. However, as we are still traversing in the unknown genetic territory, gene expression at the transcript level in dinoflagellates cannot be completely overlooked.…”
Section: Translational Control In Dinoflagellates and Its Implicationmentioning
confidence: 99%
“…It appears that sxtA may not be strongly regulated at the transcriptional level in A. minutum, as toxin quantities were not well correlated with transcript abundance (Perini et al, 2014). Nevertheless, sxtA was found to be significantly down regulated in a non-toxic mutant strain of A. pacificum (Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 91%
“…Only limited information is available regarding the expression and function of sxtA copies (Perini et al, 2014;Zhang et al, 2014). It appears that sxtA may not be strongly regulated at the transcriptional level in A. minutum, as toxin quantities were not well correlated with transcript abundance (Perini et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Specific studies on toxic dinoflagellate species have led to the establishment of defined gene sets likely related to toxin production (Beedessee, Hisata, Roy, Satoh, & Shoguchi, ; Cusick & Sayler, ; Hackett et al., ; Kellmann, Stüken, Orr, Svendsen, & Jakobsen, ; Kohli et al., , ; Lehnert et al., ; Meyer et al., ; Monroe & Van Dolah, ; Murray, Diwan, Orr, Kohli, & John, ; Perini et al., ; Salcedo, Upadhyay, Nagasaki, & Bhattacharya, ; Sheng, Malkiel, Katz, Adolf, & Place, ; Snyder et al., ; Stüken et al., ; Wang, ; Zhang, Zhang, Lin, & Wang, ). PKS genes are present in all dinoflagellates (Kohli et al., ) but many of the toxic metabolites produced by some dinoflagellate species are of polyketide origin (Kellmann et al., ).…”
Section: Methodsmentioning
confidence: 99%